Dual-channel vendor-buyer system with minimum purchase commitment and price-sensitive demand - Li, Bo (2014)
Supply chain system with Minimum Purchase Commitment (MPC) could demonstrate interesting behavior when the demand is influenced by retail price. In this dissertation, a dual-channel vendor-buyer system is analyzed with MPC policy and price-sensitive demand. For the two channels, the direct channel is shipping from the vendor’s central distribution center (CDC) directly to the buyer’s warehouse, and the indirect channel is shipping from the CDC via vendor’s regional distribution center (RDC) to the buyer’s warehouse. Based on the MPC policy, the order can be divided between these two channels with a fixed portion from direct channel and the other flexible portion from the indirect channel. To address the cost and profit issues in this system, a simulation model in MATLAB is established and simulation runs are conducted to analyze the system behavior in addition to analytical reasoning. Expected profit of the supply chain system is defined as the target function; MPC coefficient (z) and retail price (p) are selected as the variables since they determine the profit and its components. The effects of system parameters such as procurement unit cost are examined to suggest potential risk and opportunity. Profit split between the buyer and the vendor is also studied. It is concluded that pricing is the major factor in profit sharing and a lower z value is preferred by both parties.